Retrospective genomic analysis of the first Lumpy skin disease virus outbreak in China (2019) - Wei, Yu-Rong; Ma, Wen-Ge; Wang, Ping; Wang, Wen; Su, Xiao-Hui; Yang, Xue-Yun; Mi, Xiao-Yun; Wu, Jian-Yong; Huang, Jiong (Frontiers in Veterinary Science, 2023)
Lumpy skin disease caused by Lumpy skin disease virus (LSDV) is a severe systemic disease affecting cattle and other ruminants. Lumpy skin disease was first reported in northwest China in August 2019 and has severely threatened the cattle breeding industry in China. However, there have been limited genomic studies of LSDV from the first outbreak and its subsequent epidemics. This study aims to characterize the comparative genomic evolution of the LSDV strain from the first outbreak in China. The etiological agent was isolated in a Madin-Darby bovine kidney cell culture and subsequently identified by PCR and Sanger sequencing of six selected genes. The genome sequence was determined using Illumina sequencing and analyzed through genome alignment and phylogenetic tree. The results showed that all six genes were successfully amplified and genetically clustered into LSDV. The virus presented the highest homology to strain China/GD01/2020, which shared 100% identities among 150 open reading frames (ORFs), and 97.1%–99.7% identities among additional 6 ORFs. Bayesian inference tree analysis revealed that the virus shared a common ancestor with LSDV strains from China and Vietnam. The study provides an additional genomic data for LSDV tracking and control in China and neighboring countries.